Inisiasi Dan Bantuan Dalam Pra Desain Dinding Penahan Tanah Untuk Sekolah Asrama Islam - Nor Hidayati; Desti Setiyowati; Khotibul Umam; Fathinatul Labibah; Mahendra Hamid Arrafi; Mochammad Qomaruddin; Supot Rattanapun (Fakultas Teknik Universitas Palangka Raya, 2026)
Daruttauhid Islamic Boarding School, located in Jepara, is located in a landslide-prone area due to its position at the foot of a steep cliff with a height of about 14 meters and only about 3 meters from the slope. On March 17, 2024, a landslide occurred which caused damage to several buildings inside the Islamic boarding school and increased the threat to the safety of students. This situation prompted the community service team from the Civil Engineering Study Program of UNISNU Jepara to carry out community service activities in the form of an initial design of a retaining wall. This initiative aims to provide technical solutions in addressing disaster risks and strengthening the institutional capacity of Islamic boarding schools in sustainable infrastructure planning. The implementation was carried out through a participatory approach, which included field surveys, slope stability analysis, geometric design of retaining walls, creation of engineering drawings, and dissemination of results to Islamic boarding school stakeholders. The outputs of this program include: technical design documents, scientific publications, media coverage, project implementation videos, and intellectual property rights registration. It is hoped that this program will reduce the potential for landslides, increase partners' understanding of the importance of retaining wall infrastructure, and support the roadmap of Nahdlatul Ulama Islamic University (UNISNU) Jepara for disaster mitigation, sustainable infrastructure, and the application of appropriate technology.